O Ensino de Permacultura no Brasil: o papel dos Cursos de Design em Permacultura (PDCs) e as contribuições da Educação Ambiental Crítica - Fossaluza, André Santachiara [UNESP]; Tozoni-reis, Marília Freitas De Campos [UNESP] (Programa de Pós-Graduação em Educação para a Ciência, Universidade Estadual Paulista (Unesp), Faculdade de Ciências, campus de Bauru., 2020)
Permaculture is a movement that seeks to plan, create and maintain sustainable human settlements and that has been especially promoted by Permaculture Design Courses (PDCs). In this article, following the analysis of a questionnaire, we present the distribution of these courses in Brazil and discuss the teaching of permaculture and its interactions with critical environmental education. Based on the answers provided by PDC educators, we analyze the courses with regard to content, fees, and the profile of educators. We have found 38 groups that offer PDCs and 210 PDC educators in Brazil, and the data have enabled us to analyze the profile of PDC educators regarding gender, race/ethnicity and income (social class). We have also been able to discuss the objectives in the PDCs, and the popularization of permaculture. The analysis indicates that permaculture teaching in Brazil is a field of dispute with heterogeneous and contradictory actions.

A permacultura é um movimento que busca planejar, criar e manter assentamentos humanos sustentáveis, sendo difundida, principalmente, pelos Cursos de Design em Permacultura (PDCs). Neste trabalho, mapeamos esses cursos no Brasil e discutimos o ensino de permacultura e seu diálogo com a educação ambiental crítica, por meio dos resultados obtidos após a aplicação de um questionário. A partir das respostas de educadores/as de PDCs, analisamos esses cursos quanto aos seus objetivos, valores de inscrição e perfil dos/as educadores/as. Encontramos 38 grupos que oferecem PDCs e 210 educadores/as atuantes no Brasil, cujos dados permitiram compreender seu perfil quanto a gênero, à raça/etnia e à renda (classe social), assim como discutir os propósitos desses cursos e a popularização da permacultura. As análises nos permitem dizer que o ensino de permacultura no Brasil se configura como um campo de disputa, com ações de caráter contraditório e heterogêneo.
Permaculture Teaching in Brazil: the role of Permaculture Design Courses (PDCs) and the contributions of Critical Environmental Education
Keywords: Permaculture; Environmental education; Socio-environmental agriculture; Sustainable society; Permacultura; Agricultura socioambiental; Educação ambiental; Sociedade sustentável